Asas Faham Pentadbiran Pendidikan Islam: Makna Tadbir al-Ta’dib - Jamil, Asyraf Isyraqi; Wan Abdullah, Wan Suhaimi; Darusalam, Ghazali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2012)
Despite the ongoing discourse in Islamic educational administration, a deep scrutiny into the discourse reveals a more comprehensive and fundamental concept in the field. The paper aims to present the result of that scrutiny. Through semantic studies of two Arabic keywords; tadbir and ta’dib, the paper will demonstrate how the theory of tadbir al-ta`dib is constructed. As tadbir is the essence of Islamic administration and ta’dib is the essence of Islamic education, understanding these two keywords will contribute a lot in formulating the foundation of Islamic educational administration.